Social representations of colonialism in Africa and in Europe: Structure and relevance for contemporary intergroup relations. (January 2018) - Licata, Laurent; Khan, Sammyh S.; Lastrego, Simona; Cabecinhas, Rosa; Valentim, Joaquim Pires; Liu, James H.
Abstract: European colonial powers invaded and then dominated a large part of the African continent from the sixteenth to the twentieth century. The influence of colonialism did not cease after independence as it still impregnates the cultures and identities of both formerly colonising and formerly colonised peoples. The question of how inhabitants of formerly colonised and formerly colonising countries represent the colonial past is a key issue in understanding this lasting influence. Social representations of European colonial action were investigated among young people ( N  = 1134) in three European countries and six African countries. Social representations of the colonial past were structured around two main dimensions across African and European samples: Exploitation and Development. Social representations of colonialism denoted by Exploitation were more strongly endorsed by the European compared to the African subsample, whereas those denoted by Development were more strongly endorsed by the African compared to the European subsample. However, while African participants considered colonialism less negatively than Europeans, they also had higher expectations concerning Europeans' collective guilt feeling and willingness to offer reparations. By contrast, European participants' social representations of colonialism were more negative but they were less likely to believe that present-day European peoples and governments are accountable for the misdeeds of colonialism in the past. Finally, national identification mediated the association between the Exploitation dimension of colonialism and both group-based emotions and support for reparation in the African, but not the European, subsample.